Pengaruh Fitur Aplikasi Terhadap Kepuasan Kerja Driver Maxim Di Kota Makassar - Akbal Akbal; H Andi saharuddin; Hasiah Hasiah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
AKBAL, 2024.The purpose of this study is to find out how application features have an impact on the job satisfaction of Maxim drivers in the city of Makassar. This study uses a quantitative approach with a total of 91 respondents. The driver is sampled by saturation or probability sampling techniques. The results show that the application feature variable has a positive impact on driver satisfaction, with the t-count value being greater than the t-table (15.172 greater than 0.677) and the significant value being less than 0.05 (0.000 lower than 0.05) features.